Optimasi Kombinasi Karbopol 940 dan HPMC Terhadap Sifat Fisik Gel Ekstrak dan Fraksi Metanol Daun Kesum (Polygonum minus Huds.) dengan metode Simplex Lattice Design - Sari, Rafika; Nurbaeti, Siti Nani; Pratiwi, Liza (UI Scholars Hub, 2016)
Indonesia especially Kalimantan Barat well known by its biodiversity, one of the potential resource is Kesum leaves. Kesum leaves are potential by its antibacterial effect, so that it can be formulated into pharmaceutical dosage form, especially gel. This research aims to know the best comparison between Carbopol 940 and Hydroxypropyl methylcellulose (HPMC) gel base affecting the physical stability of methanol extract and fraction of kesum leaves gel by Simplex Lattice Design (SLD) method. Gels were prepared into three variation base such as gel A (100% Carbopol - 0% HPMC); gel B (0% Carbopol - 100% HPMC); and gel C (50% Carbopol – 50% HPMC). According to SLD method, the optimum combination obtained among the basis were 100% Carbopol - 0% HPMC for Kesum leaves methanol extract gel and 10% Carbopol – 90% HPMC for Kesum leaves methanol fraction gel. Then , the gels were tested their physical stability including adhesive ability spreadability and pH. Results were analyzed using One sample t- test and was known there was no difference of the physical stability between Kesum leaves methanol extract gel and Kesum leaves methanol fraction gel.